2002
DOI: 10.1258/0956462021924776
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium - an up-date

Abstract: Summary:Mycoplasma genitalium was ® rst isolated from men with non-gonococcal urethritis (NGU) more than 20 years ago. Use of polymerase chain reaction technology has shown it to be a cause of acute NGU and probably chronic NGU, almost independently of Chlamydia trachomatis, but there is no substantial evidence that it causes acute or chronic prostatitis. In women, M. genitalium is not associated with bacterial vaginosis, but it is strongly associated with cervicitis and endometritis and serologically with sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
0
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 54 publications
3
78
0
10
Order By: Relevance
“…[2][3][4][5][6][7][8] There is also increasing evidence that M genitalium causes mucopurulent cervicitis in women 9 and that it may cause endometritis 10 11 and possibly tubal infection with sequelae in the form of ectopic pregnancy or tubal infertility.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7][8] There is also increasing evidence that M genitalium causes mucopurulent cervicitis in women 9 and that it may cause endometritis 10 11 and possibly tubal infection with sequelae in the form of ectopic pregnancy or tubal infertility.…”
mentioning
confidence: 99%
“…Azithromycin is at least 100-fold more active in vitro against M. genitalium than any of the fluoroquinolones or tetracyclines. 18 In one study, M. genitalium eradication rates in women treated with azithromycin were 88% compared with 37% with doxycycline. 19 Azithromycin is available locally, and the treatment cost for 1 g in Haiti ranges from 40 to 200 Haitian Gourdes (US $0.93-$4.65).…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the M. genitalium load was significantly higher in men with acute nonchlamydial NGU than in asymptomatic men (17). The various results reported to date suggest that M. genitalium may be associated with the development of acute NGU independent of Chlamydia trachomatis (2,13).…”
mentioning
confidence: 81%